El rol de los eclesiásticos en la construcción de la legitimidad “internacional” de la dinastía portuguesa de los Avis (1383-1433) - Néstor Vigil Montes (Medievalista)
The accesion to the throne of the Portuguese Avis dynasty embodied in the person of John I of Portugal implied the need to carry out diplomatic initiatives aimed at guaranteeing the survival, which involved achieving the legitimation of the new political situation. Distinguised ecclesiastics linked to the administration of the kingdom, among which was João Afonso Esteves de Azambuja or Rui Lorenço, put their knowledge, experience and prestige at the service of the demands of the diplomatic program of the new dynasty. Scarce and appreciated human resources that they could not cover all the fields of action of the John I of Portugal’s foreign policy, reason why they specialized in three questions: the negotiations with the pontificate to legitimize John I of Portugal, the construction of peace with the Kingdom of Castile, and the participacion in the ecumenical councils that led to a solution for the Great Occidental Schism. Hard and persistent negotiators who took advantage of these diplomatic assignments to advance in their ecclesiastical career by achieving ecclesiastical benefits, sometimes offered by a Pope, which tried to win their favor, and other times offered by their monarch as recognition after successfully achieving the diplomatic objectives.